Karakteristik Morfometrik Juvenil Ikan Baronang Totol (Sigannus guttatus) pada Akuakultur Multi Tropik Berbasis Feeding Rate - Heriansah, Heriansah; Rukmini Kustam, Sri; Sahriyanti , Andi; Tri Hidayani, Mesalina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Information on morphometrics has been widely used for catches. This study aims to determine the morphometric characteristics of rabbitfish in a multi-trophic system cultivation based on feeding rate. Rabbitfish are maintained in an integrated manner with green mussels, sea urchins, and seaweed. The study was conducted for 6 weeks at the Laboratory of the Balik Diwa Maritime Technology and Business Institute, Makassar. Three feeding rate treatments of 5%, 7.5%, and 10% each with three replications were given to rabbitfish with a frequency of 4 times a day. During maintenance, a closed water circulation process was carried out and continuous aeration was provided in each container. The results showed that the total length at feeding rates of 5%, 7.5%, and 10% were 5.3 cm, 7.1 cm, 8.1 cm, respectively, and the standard length was 4.1 cm, 5.8 cm, and 6.7 cm, respectively. Meanwhile, the height of each body was 1.8 cm, 2.1 cm, and 2.6 cm. Analysis of variance showed that these three morphometric variables were significantly affected by feeding rate, and the three levels of feeding rate were significantly different (P<0.05). Water quality during maintenance was in the range that could be tolerated by rabbitfish. Temperature was in the range of 26.0-28.6°C, salinity 25.1-28.5 ppt, dissolved oxygen 5.2-7.1 mg/L, pH 7.6-8.0 and ammonia 0.032-0.095 mg/L. The morphometric characteristics of rabbitfish in multi-trophic system cultivation increased significantly along with the increase in feeding rate.